Lanthanide complexes as molecular dopants for realizing air-stable n-type graphene logic inverters with symmetric transconductance. Issue 4 (15th January 2019) - Gajarushi, Ashwini S.; Wasim, Mohd; Nabi, Rizwan; Kancharlapalli, Srinivasu; Rao, V. Ramgopal; Rajaraman, Gopalan; Subramaniam, Chandramouli; Shanmugam, Maheswaran
Abstract : In this communication we have unveiled the importance of lanthanide dopant, to realize n-doping of GFETs with an exceptional ambient stability and enhanced mobility. An unconventional mechanism proposed for such phenomenon is well supported by various analytical methods and rationalized by computational calculations. Abstract : An unprecedented air-stable, n-doped graphene field-effect transistor (GFET) with exceptionally enhanced mobility (500%), and concomitantly increased current density (∼10 5 A cm −2 ), using lanthanide macrocyclic complexes [Ln(L1 )(NO3 )3 ] (where Ln = La (1 ) or Ce (2 )) is demonstrated. Such n-doped GFETs (n-GFETs) exhibit ambient stability for up to 7200 h, attributed to the inherent robustness of1 and2 . Achieving stable and symmetric n-GFETs is mutually exclusive and elusive, underlining the significance of both high stability and symmetric electron- and hole-currents illustrated here. Interestingly, the influence of C–H⋯π interaction for the non-covalent charge-transfer between the dopant and GFET is established experimentally for the first time and strongly corroborated through computational investigations. Besides stabilizing n-doped GFETs, the C–H⋯π interaction unravels a previously unknown direction for electronic tuning of graphene. Importantly, spatial selectivity is achieved through sub-monolayer coverage (0.5–3.0 molecules per μm 2 ) of the dopants using the femtojet dispensing route. This approach is synergistically combined with the air-stability of n-GFETs to realise complementary, bottom-gated logic inverters exhibiting the highest gain of 0.275 (at 2 V) and lowest power dissipation (∼30 μW), to realise next-generation molecular electronic devices.